2000
DOI: 10.1097/00000539-200003000-00024
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Epidural Analgesia with 0.125% Ropivacaine with Fentanyl Versus 0.125% Bupivacaine with Fentanyl during Labor

Abstract: By using a patient-controlled epidural analgesia technique, ropivacaine 0.125% with fentanyl 2 microg/mL produces similar analgesia with significantly less motor block than a similar concentration of bupivacaine with fentanyl during labor. Whether this statistical reduction in motor block improves clinical outcome or is applicable to anesthesia practices which do not use the patient-controlled epidural analgesia technique remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(60 citation statements)
references
References 15 publications
5
54
0
Order By: Relevance
“…Similarly, during the second stage of labor also VAS score was comparable at any time. Meister et al [14] and Clément et al [11] observed that VAS score was comparable in both the groups throughout the labor. In this study, Apgar score was between 7 and 10 in most of the neonates, 93.33% in Group B and in 100% in Group R at 1 min and at 5 min and 6.67% neonates in Group B and no neonate in Group R had Apgar score between 5 and 6 at 1 min and at 5 min.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 91%
See 2 more Smart Citations
“…Similarly, during the second stage of labor also VAS score was comparable at any time. Meister et al [14] and Clément et al [11] observed that VAS score was comparable in both the groups throughout the labor. In this study, Apgar score was between 7 and 10 in most of the neonates, 93.33% in Group B and in 100% in Group R at 1 min and at 5 min and 6.67% neonates in Group B and no neonate in Group R had Apgar score between 5 and 6 at 1 min and at 5 min.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 91%
“…In this study, there was no incidence of pruritus in either group. Chua et al [16] observed that none of the patients in either group (bupivacaine 0.125% and ropivacaine 0.125%) developed pruritus whereas Meister et al [14] observed that 56% patients of ropivacaine/ fentanyl group and 52% patients of bupivacaine/fentanyl group complained of pruritus, which did not require any treatment. In this study, 10% of patients in Group B and 6.7% in Group R had intrapartum urinary retention (patients catheterized with K-90 catheter).…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Mesiter et al, 4 where 102.5 ± 82 mg of 0.125% bupivacaine required against 113.0 ± 43.3 mg of 0.125% ropivacaine.…”
Section: Total Dose Of Local Anaesthetic Requiredmentioning
confidence: 99%
“…Several individual studies using low concentrations of local anaesthetic (£ 0.125%) however did demonstrate differences in motor block with ropivacaine producing less motor block then bupivacaine (173)(174)(175)(176)(177)(178)(179)(180)(181). Gautier et al clearly demonstrated that, especially if the cumulative epidural dose of local anaesthetic increased, the risk of motor block was increased with bupivacaine (175).…”
Section: Excellent Labour Analgesia With Minimal Side-effectsmentioning
confidence: 99%